Binaural hearing: Physiological and Clinical View - Bipin Kishore Prasad (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
The main difference between the two ears is that they are not in the same place [1]. Use of both the ears to perceive the world of sound around us is defined as Binaural hearing. Just as we use two eyes to see in three dimensions, we use two ears for "dimensional hearing". Binaural hearing is literally opposite of monaural hearing. It allows us to (a) 'map' the sound in space, (b) pick out soft sounds, (c) pick out distant sound or speech and (d) separate a single voice  from surrounding background noise. Among the mammals, human is considered to be the one gifted with most developed  communication skill.